Dynamic Mechanical Hysteresis of Magnetorheological Elastomers Subjected to the Cyclic Loading and Periodic Magnetic Field - Zhang, Yunfei; Fang, Fengzhou; Huang, Wen; Chen, Yuchuan; Qi, Song; Yu, Miao (Frontiers in Materials, 2019)
Magnetorheological elastomer (MRE) is a kind of the most promising smart materials with excellent magnetic-control mechanical properties. This work focuses on the study of the dynamic mechanical properties of MRE under cyclic loadings and periodic magnetic field. The influences of matrix, particle distribution, magnetic field on the dynamic mechanical hysteresis were systematically investigated. It was found that all the normal force, magnetic fields and shear strain would cause a hysteresis in the dynamic mechanical responses of MRE. The continuous cycle tests revealed the hysteresis tended to be saturated after several initial cycles. The hysteresis of MRE under the constant magnetic field can be attributed to the rearrangement of particles, which caused a hardening effect of MRE under the continuous dynamic tests. The periodic magnetic field caused a hysteresis in the dynamic modulus which could be attributed to the irreversible movement of the particles. Among them, the polymer matrix of MRE played an important role in the dynamic mechanical hysteresis, which suggested more stable molecular chain structures in the matrix would reduce the magnitude of hysteresis and improve its stability. Besides, the saturation of the mechanical hysteresis had also been studied, and then relevant physical mechanism was proposed for the qualitative explanation.